Še ena koščena konica iz Potočke zijalke - Brodar, Mitja (Arheološki vestnik, 1994)
A previously unknown bone collection from Potočka zijalka discovered by J. Gros has recently been presented to the "Landesmuseum ftir Karnten" in Klagenfurt. A bone point from the collection is discussed.